A NEW SPECIES OF NEPENTHES (NEPENTHACEAE) FROM SUMATRA - Pitra Akhriadi; Hernawati Hernawati; Rusjdi Tamin (Research Center for Biology, 2004)
AKHRIADI, PITRA, HERNAWATI & TAMIN, RUSJDI. 2004. A new species of Nepenthes(Nepenthaceae) from Sumatra. Reinwardtia 12 (2): 141 – 144. - A NewSpecies of Nepenthes rigidifolia is described.